A. Transparansi Transparansi Pemerintah Desa Terhadap Pengelolaan Dana Desa di Desa Lombo Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Syawal Kurniawan; Nurjannah Nonci; Haeruddin Syarifuddin (Universitas Warmadewa, 2025)
This study aims to examine the level of transparency in village government related to the management of village funds in Lombo Village, Pitu Riase Subdistrict, Sidenreng Rappang Regency, and to identify the factors influencing it. This research employed a descriptive quantitative approach with data collected through observation, questionnaires, literature studies, and documentation. The sample consisted of 77 respondents selected randomly from a total of 338 households. The results indicate that the level of transparency in the management of village funds is considered good, as evidenced by open access to budget information, community participation in decision-making, and regular financial reporting. Factors affecting transparency include timely access to accurate information, clear procedures and cost structures, and the availability of grievance mechanisms. The study concludes that there is a positive and significant relationship between government transparency and effective village fund management. Enhancing transparency is therefore expected to strengthen accountability and public trust in village governance.